Organizational factors associated with occupational stress among lecturers in Community Colleges, Peninsular Malaysia - Ismail, Nada; Abdul Rahman, Anita; Zainal Abidin, Emilia (Tehran University of Medical Sciences, 2014)
Background: A cross sectional study conducted to identify the organizational factors associated to the occupational stress among lecturers in selected Community Colleges, Peninsular Malaysia. Methods: Study was conducted by using cluster-sampling method and 189 self-administrated questionnaires were distributed. A validated Malay version of Job Content Questionnaire (JCQ) was used to obtain the information regarding respondent’s background and their respective job scope. JCQ described four organizational factors that were decision latitude, psychological job demand, social support and job insecurity. Results: Response rate was 87.1% with 25.9% of the lecturers were stressed. There were no significant association between occupational stress with any socio-demography factors but the result showed significant associations between occupational stress and all four organizational factors studied, decision latitude (P<0.001); psychological job demand (P<0.001); social support (P<0.001); and job insecurity (P<0.001). Conclusion: From the result, it clearly showed that stress among lecturers came from organizational factors in their workplace. The highest organizational factors reported were insufficient social support from the employer and limited authority in decision making. These factors might cause lack of communication and poor social interaction. The occupational stress among lecturers was associated with all the organizational factors (decision latitude, psychological job demand, social support and job insecurity) in this study. Therefore, preventive measures or intervention programs need to be implemented in Community Colleges to alleviate the negative consequences.